Towards an Empirical Unified Crust–Core Description of Neutron Stars. (24th October 2017) - Chatterjee, Debarati; Gulminelli, Francesca
Abstract: Understanding the properties of the crust and the core as well as its interface is essential for accurate astrophysical modelling of phenomena such as glitches, X-ray bursts or oscillations in neutron stars. To study the crust–core properties, it is crucial to develop a unified and consistent scheme to describe both the clusterised matter in the crust and homogeneous matter in the core. The low density regime in the neutron star crust is accessible to terrestrial nuclear experiments. In order to develop a consistent description of the crust and the core of neutron stars within the same formalism, we use a density functional scheme, with the model coefficients in homogeneous matter related directly to empirical nuclear observables. In this work, we extend this scheme to non-homogeneous matter to describe nuclei in the crust. We then test this scheme against nuclear observables.